Clinical feature difference between juvenile amyotrophic lateral sclerosis with SPTLC1 and FUS mutations. Issue 2 (20th January 2023) - Wang, Peishan; Wei, Qiao; Li, Hongfu; Wu, Zhi-Ying
Abstract: Background: Juvenile amyotrophic lateral sclerosis (JALS) is an uncommon form of amyotrophic lateral sclerosis whose age at onset (AAO) is defined as prior to 25 years. FUS mutations are the most common cause of JALS. SPTLC1 was recently identified as a disease-causative gene for JALS, which has rarely been reported in Asian populations. Little is known regarding the difference in clinical features between JALS patients carrying FUS and SPTLC1 mutations. This study aimed to screen mutations in JALS patients and to compare the clinical features between JALS patients with FUS and SPTLC1 mutations. Methods: Sixteen JALS patients were enrolled, including three newly recruited patients between July 2015 and August 2018 from the Second Affiliated Hospital, Zhejiang University School of Medicine. Mutations were screened by whole-exome sequencing. In addition, clinical features such as AAO, onset site and disease duration were extracted and compared between JALS patients carrying FUS and SPTLC1 mutations through a literature review. Results: A novel and de novo SPTLC1 mutation (c.58G>A, p.A20T) was identified in a sporadic patient. Among 16 JALS patients, 7/16 carried FUS mutations and 5/16 carried respective SPTLC1, SETX, NEFH, DCTN1, and TARDBP mutations. Compared with FUS mutation patients, those with SPTLC1 mutations had an earlier AAO (7.9 ± 4.6 years vs. 18.1 ± 3.9 years, P  < 0.01), much longer disease duration (512.0 [416.7–607.3] months vs. 33.4 [21.6–45.1] months, P  < 0.01), and no onset of bulbar. Conclusion: Our findings expand the genetic and phenotypic spectrum of JALS and help to better understand the genotype–phenotype correlation of JALS.